Gathering Prey : Lucas Davenport #25 - Sandford, John, 1944 February 23- (New York : G. P. Putnam's Sons, 2015)
When his adopted daughter's friend reports that someone has been killing off a circle of nomadic panhandlers, Lucas travels to North Dakota, where he encounters a dangerously violent subculture.
When his adopted daughter's friend reports that someone has been killing off a circle of nomadic panhandlers, Lucas travels to North Dakota, where he encounters a dangerously violent subculture.
Keywords: Davenport, Lucas (Fictitious character) -- Fiction; Private investigators -- Minnesota -- Minneapolis -- Fiction; Homeless persons -- Crimes against -- Fiction; Serial murder investigation -- Fiction; FICTION / Crime; FICTION / Suspense; FICTION / Mystery & Detective / General; Davenport, Lucas (Fictional character) -- Fiction; Detectives -- Minneapolis (Minn ) -- Fiction; Homeless persons -- Fiction; Serial killers -- Fiction; Criminal investigation -- Fiction; Mystery fiction